Universal secondary education in the OECS : policy and access, quality and rewards : [a paper for discussion) - Hinds, Henry (OECS [Castries]LC, 2007)
Examines the components of universal secondary education and its implications for ministry level administrative officials, professional educators at the central ministry offices and at the school (and district) level. Examines also the resource implications as well as the social legitimation complexities of implementing universal access.